Geology of the United States' seafloor : the view from GLORIA - Gardner, James V.; Field, Michael E.; Twichell, David C. (Cambridge University Press, 1996)
Geology of the United States' Seafloor presents new, definitive studies of the seafloor adjacent to the United States - the west coast, east coast, Alaskan margin, Gulf of Mexico and the Caribbean - from the GLORIA long-range sidescan sonar images, and complementary seismic profiling, and magnetic surveys. This spectacular dataset has provided a new insight into the structural evolution of the seafloor, and the sedimentary processes that have modified it. Such comprehensive interpretation of the images, in the context of the geology and geological processes of the seafloor, has not been presented before. New concepts have emerged and much new knowledge garnered as a result of this surveying. Geology of the United States' Seafloor will be useful to the broad range of scientists studying the continental margins and the seafloor of the world.